Social Media and the COVID-19 Disinfodemic in the Digital Space: Disempowering the Public and Threatening Public Health - Chikandiwa, Christopher Tarisayi; Zviyita, Itai; Mapudzi, Hatikanganwi (Acta Universitatis Danubius. Communicatio, 2022)
Social media have become one of the fastest platforms in terms of providing the public with timely news coverage on disasters and many other things. However, little is known about the nature and direction of the influence of the explosion of disinfodemic in the digital space. This article seeks to establish the extent of COVID-19 disinfodemic in the cyber sphere, with particular reference to the African context. A purposive (judgemental) sampling of archival data was done, followed by a thematic content analysis. The findings of the study indicated misconceptions about the origins of the virus, as well as the diagnosis, treatment, prevention and cure of the COVID-19. False and misleading statistics about the COVID-19 disease were also noted. This article is valuable as it does not only bring together the role of social media during the COVID-19 in the African continent, but it also calls for the reconceptualisation of social media and advocates for the dissemination of information in a responsible way.